2006
DOI: 10.1007/s11461-006-0046-0
|View full text |Cite
|
Sign up to set email alerts
|

Water-holding characteristics of litter in different forests at the Lianxiahe watershed

Abstract: We surveyed the forest litter amount at the Lianxiahe watershed in the Three Gorges Reservoir Area and analyzed some hydrological characteristics such as the maximum water-holding capacity and water absorption rate of litter in six types of forests, i.e. the Cupressus funebris forest, the coniferous mixed forest, the coniferous and broad-leaved mixed forest, the broad-leaved forest, the Pinus massoniana forest, the bush forest. Results showed that the litter amount follows the order of the coniferous and broad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…Due to the large macroporosity of litter, depending on the size of organic particles in its composition (Ilek et al 2017), water retention in this horizon occurs mainly through the adsorption and absorption of water through undecomposed organic matter. Zhang et al (2006) found that the rate of water absorption by undecomposed litter of various types of stands decreases rapidly in the first 6 hours of soaking; and in the first 8 hours in the case of partially decomposed litter. In both cases, most of the water was absorbed in the initial period of soaking, and the influence of the type of stand on the absorption rate was hardly noticeable.…”
Section: Figurementioning
confidence: 97%
See 1 more Smart Citation
“…Due to the large macroporosity of litter, depending on the size of organic particles in its composition (Ilek et al 2017), water retention in this horizon occurs mainly through the adsorption and absorption of water through undecomposed organic matter. Zhang et al (2006) found that the rate of water absorption by undecomposed litter of various types of stands decreases rapidly in the first 6 hours of soaking; and in the first 8 hours in the case of partially decomposed litter. In both cases, most of the water was absorbed in the initial period of soaking, and the influence of the type of stand on the absorption rate was hardly noticeable.…”
Section: Figurementioning
confidence: 97%
“…Litter plays an important role in water infiltration into the soil profile, prevents erosion, slows down stemflow and limits evaporation from deeper soil horizons (Onda & Yukawa 1994, Tamai et al 1998, Greiffenhagen et al 2006). Its water storage capacity depends not only on the quantitative share of individual litter components, such as leaves, needles and branches, but also on the bulk density, total porosity and species composition of the stand (Laurén & Mannerkoski 2001, Zhang et al 2006, 2009, Ilek et al 2015.…”
Section: Introductionmentioning
confidence: 99%
“…6). Similarly, Zhang et al (2006) showed that the water storage capacity of the litter of coniferous stands is greater than that of deciduous ones. Leuschner (1998) showed differences in the formation of the water storage capacity of organic horizons between beech, oak and pine stands.…”
Section: Capillary Capacitymentioning
confidence: 99%
“…The water storage capacity of the organic horizons of forest soils is affected by a number of factors, such as the type and degree of decomposition of organic matter (Zhang et al 2006;Kucza 2007;Tsiko et al 2012) and the wettability of the soil material (Prusinkiewicz and Kosakowski 1986). Putuhena and Cordery (1996), Sato et al (2004) and Li et al (2013) found that the water content of the forest litter has a linear relationship with respect to its mass.…”
Section: Introductionmentioning
confidence: 99%
“…In turn, this probably resulted in a reduction of the litter water storage capacity and degree of saturation, despite the slight impact of pine needle admixture on changes in bulk density of the litter and its porosity (compared to pure oak litter). Some studies indicated that mixed litter had a higher water storage capacity than pure coniferous litter [33], but mixed coniferous-broadleaved litter usually showed a lower water storage capacity than mixed coniferous litter [55,56]. Mixed stands also influence other properties of the litter.…”
Section: Discussionmentioning
confidence: 99%